The Role of Science in Handling Stunting in Selengen Village, Kayangan District - Taufik, M.; Hamdani, Muh; Azri, Saepul; Jati, Indra; Hadi, Samsul; Isnayadi, Raden (Abdi Masyarakat, 2024)
The role of science is the main focus discussed in this paper. Knowledge is something that ordinary people must have, such as knowledge about how to care for children in terms of parenting, food, and things that must be paid attention to in terms of a child's health. The aim is so that parents understand how to deal with stunting through science. The reason we took this topic because we brought the theme from the STKIP Hamzar campus with the theme "Making North Lombok Free from Child Marriage and Zero Stunting. This research aims to describe the role of science in handling stunting in Selengen village. The research uses a qualitative approach with data collection techniques from interviews and observations. The research subjects involved Health Midwives, Nutrition Midwives, Gynecology Midwives, and cadres in the local village. The scope of activities such as outreach on the provision of supplementary food (PMT) and immunization.